Pre-storage calcium salts treatment maintained postharvest quality and bioactive compounds of fresh jujube fruit - Farid Moradinezhad; Mehdi Ghesmati; Mehdi Khayat (Fundamental and Applied Agriculture, 2019)
Jujube fruit is quickly damaged and it has a short shelf life in ambient temperature mainly due to senescence and flesh browning. The effects of postharvest calcium salts on quality attributes and physico-chemical characteristics of fresh jujube fruit were investigated with four replications. Fresh jujube fruits at crisp mature (whitish red) stage were picked from a local commercial jujube orchard during early in August in Birjand. Uniform fruits were then selected and immersed in solutions of different calcium sources (calcium chloride, calcium nitrate and calcium sulfate) at two concentrations (0.5 and 1%) or distilled water as control for 5 minutes, air-dried and then stored in cold storage for 50 days. The physico-chemical and sensory quality attributes of fresh fruit were evaluated at the end of storage time. The results showed that weight loss and pH was not influenced by the calcium salt solutions, whereas immersion of jujube fruits in different concentrations of calcium salts had a significant effect on the firmness of the fruit tissue. Calcium salts treatment significantly reduced fruit decay and shrinkage. In addition, postharvest dipping in calcium chloride and calcium nitrate solutions preserved nutritional value (ascorbic acid and total phenolic content) and maintained the sensory quality of fresh jujube fruit. Postharvest calcium salts application preserved the bioactive compounds, quality and improve the overall acceptability of jujube fruit, especially at a concentration of 1% of both salts. However, to determine the proper concentration of calcium salts and the time of dipping treatment for practical applications further studies are required. [Fundam Appl Agric 2019; 4(3.000): 890-897]